Design and Construction of an Anti-Sleep Alarm System for Drivers. - Twongirwe, Isaac (Kabale University, 2024)
The prevalence of road accidents due to driver drowsiness necessitates the development of effective anti-sleep alarms. This report details the design and construction of an anti-sleep alarm intended to mitigate drowsiness among drivers. The system integrates a sensor to monitor physiological and behavioral indicators of drowsiness, coupled with a microcontroller to process data and activate alerts. This approach enhances reliability and provides a robust solution to driver fatigue and drowsiness.